2019
DOI: 10.21315/apjee2018.33.2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Students’ Academic Performance in Malaysian Online Distance Learning Institutions

Abstract: The increasing number of learner failure rates are alarming in online distance learning. Previous studies have identified the factors that have contributed to online distance learning students' failure as lack of time and lack of motivation. The purpose of this study is to develop a direct effect understanding of extrinsic motivation, intrinsic motivation, self-efficacy and time management on students' academic performance in an online distance learning institution in Malaysia. The Structural Equation Model (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Institutional support in designing and providing infrastructure and technology is also recognised as critical for transition to enhanced BL (e.g. Graham et al, 2013;Adekola et al, 2017;Mohd Fadzil, 2020;Osman et al, 2018;Tang & Intai, 2017). Similarly, the 'support' category in Graham et al's BL Adoption Framework includes institutional implementation and maintenance of its BL design, technical and pedagogical support staff, and for staff incentives (Graham et al, 2013).…”
Section: Infrastructure and Relevant Technologymentioning
confidence: 99%
“…Institutional support in designing and providing infrastructure and technology is also recognised as critical for transition to enhanced BL (e.g. Graham et al, 2013;Adekola et al, 2017;Mohd Fadzil, 2020;Osman et al, 2018;Tang & Intai, 2017). Similarly, the 'support' category in Graham et al's BL Adoption Framework includes institutional implementation and maintenance of its BL design, technical and pedagogical support staff, and for staff incentives (Graham et al, 2013).…”
Section: Infrastructure and Relevant Technologymentioning
confidence: 99%
“…Various studies have shown mixed results on the relationship between academic performance with critical predictive factors of online learning such as satisfaction, self-efficacy, social interactive engagement, and environment. Recent local studies (Lilian et al, 2021;Azzieatul & Lai, 2021;Karim et al, 2021;Zahir et al, 2018) have suggested a positive relationship between academic achievement and online learning readiness. Most of these studies showed optimistic narratives of student readiness that had a positive impact on their performance, which coincidentally, was based on perceived academic performance.…”
Section: Academic Performance With Predictive Factors For Effective O...mentioning
confidence: 99%
“…This surge is contributed by the advancement of learning technologies and the shift towards 21st century learning (Miller, 2018). Prior to this, the use of e-learning is limited to institutions that offer distance learning programmes (Osman et al, 2018). As technological devices and tools become more cost-effective and the internet network coverage is expanded, the implementation of e-learning in higher education can be seen to be more wide-ranging.…”
Section: Literature Review E-learning In Higher Educationmentioning
confidence: 99%